Feasibility of collecting tumor samples of breast cancer patients diagnosed up to 50 years ago in the Child Health and Development Studies. (6th March 2017) - Krigbaum, N. Y.; Rubin, R. A.; Cirillo, P. M.; Terry, M. B.; Habel, L. A.; Morris, C.; Cohn, B. A.
Abstract : Environmental exposures during pregnancy may increase breast cancer risk for mothers and female offspring. Tumor tissue assays may provide insight regarding the mechanisms. This study assessed the feasibility of obtaining tumor samples and pathology reports from mothers (F0) who were enrolled in the Child Health and Development Studies during pregnancy from 1959 to 1967 and their daughters (F1) who developed breast cancer over more than 50 years of follow-up. Breast cancer cases were identified through linkage to the California Cancer Registry and self-report. Written consent was obtained from 116 F0 and 95 F1 breast cancer survivors to access their pathology reports and tumor blocks. Of those contacted, 62% consented, 13% refused and 24% did not respond. We obtained tissue samples for 57% and pathology reports for 75%, and if diagnosis was made ⩽10 years we obtained tissue samples and pathology reports for 91% and 79%, respectively. Obtaining pathology reports and tumor tissues of two generations is feasible and will support investigation of the relationship between early-life exposures and molecular tumor markers. However, we found that more recent diagnosis increased the accessibility of tumor tissue. We recommend that cohorts request consent for obtaining future tumor tissues at study enrollment and implement real-time tissue collection to enhance success of collecting tumor samples and data.